The father of the term ‘biotechnology’ was Hungarian: The forgotten works of Károly Ereky - Gábor, Miklós Gábor; Kralovánszky, Ubul Pál (Acta Agraria Debreceniensis, 2005)
In the Nature, Robert Bud gave an account of the fact that the generator of the concept "biotechnology" was the Hungarian Karl Ereky who, in his book published in Berlin in 1919 entitled "Biotechnologie der Fleisch-, Fett- und Milcherzeugung im landwirtschaftlichen Grossbetriebe" ("Biotechnology of Meat, Fat and Milk Production in a Large-Scale Agricultural Farm"), disclosed his observations and new views in that regard. Later on, Ereky’s two essays, published in German language again, and other contemporary German sources have been processed which have confirmed the assumption whereas – in scientific terms – the further first applications of the expression "biotechnology" can be attributed to Ereky’s works. Recently, we have explored and found biographical sources and documents which had been published by Ereky, which, however, have already been forgotten, by dint of which the story of origin of the first concept "biotechnology" can as well be clarified in a factual manner.